ROLE OF LIVER FUNCTION TESTS IN SYMPTOMATIC CHOLELITHIASIS - Habib, Lubna; Mirza, Masoom Raza; Channa, Muhammad Ali; Wasty, Wajahat Hussain (Journal of Ayub Medical College Abbottabad, 2009)
Background: Cholelithiasis is a common problem in west as well as in developing nations and its incidence is continuously rising. It has become routine to order LFT's in every patient undergoing cholecystectomy for symptomatic cholelithiasis. Objective: To evaluate the usefulness of routine Liver Function Tests (LFT's) in patients with symptomatic cholelithiasis. Methods: This prospective descriptive study was conducted from August 2006 to July 2007 at Department of Surgery, Hamdard University Hospital and other private hospitals. All patients presenting with symptomatic cholelithiasis with no past and present history of jaundice, pancreatitis, cholangitis and normal calibre common bile duct on ultrasonography. The relevant data regarding history, clinical examination, LFT's and ultrasound findings were recorded and analysed. Results: Out of 124 patients, 102 (82.25%) were female and 22 (17.74%) were male with the mean age 43 years (range 20 to 76 years). Majority of patients, 110 (88.71%) presented as chronic calculous cholecystitis, 12 (9.68%) as acute calculous cholecystitis and 2 (1.61%) with biliary colic. In 108 (87.10%) patients, labelled as group A, LFT's were with in normal range. In this group most of the patients, 103 (95.37%) were those who presented as chronic calculous cholecystitis. Rest of the 5 patients (4.63%) with normal LFT's were those who presented as acute calculous cholecystitis. In 16 patients (12.90%), labelled as group B, LFT's were found deranged. In this group 7 (43.75%) patients presented as acute calculous cholecystitis, 7 (43.75%) as chronic calculous cholecystitis and 2 (12.5%) with biliary colic. Bilirubin was found elevated in 2, AST in 4 and alkaline phosphatase in all patients. None of these patients in either group had dilated CBD on preoperative ultrasound examination and per operatively (in open surgery) CBD dilatation or palpable stones were not found. Conclusion: A routine LFT's in preoperative assessment of uncomplicated symptomatic cholelithiasis usually comes out normal and it is not a good predictive marker for the detection of silent CBD calculi. Keywords: Cholelithiasis, Gall stones, Choledocholithiasis, Common bile duct, Liver function test, Cholecystectomy, Laparoscopic, Symptomatic, Uncomplicated